Pemahaman Dan Sikap Masyarakat Terhadap Program Moderasi Beragama - Nazlia, Rizki; Siregar, Kholijah; Rifani, Nadra; Handani, Mira (LPPPI Publishing, 2024)
Religious moderation is a way of looking at us in moderation, namely understanding and practicing religious teachings without being extreme, whether extreme right or extreme left. This writing aims to find out initial information regarding understanding and attitudes, where the method used is descriptive qualitative with direct community observation research techniques, then the data obtained will be analyzed, classified and interpreted to obtain results that will be classified based on the value of understanding and moderation attitudes. religious. The conclusion of this writing is that several factors are found that influence public awareness of the understanding and attitude of religious moderation, namely: Insufficient education, unbalanced influence of media and information, lack of role of religious figures, local culture and traditions. Then there are several strategies to overcome the lack of understanding of religious moderation in society, namely: education, inter-religious dialogue, social media, social activities, joint religious activities, and arts and cultural activities.